Predictors of coronary artery disease in middle‐aged Taiwanese women at premenopause, postmenopause and after undergoing hysterectomy. Issue 17 (3rd June 2016) - Tsai, Ching‐Ching; Hsieh, Ming‐Hsiung; Yang, Hung‐Yu; Chan, Paul; Jeng, Chii
Abstract : Aims and objectives: To examine the predictors of coronary artery disease among middle‐aged women at various menopausal statuses. Background: Few studies have explored coronary artery disease predictors among middle‐aged women at various menopausal statuses, particularly with the inclusion of women who underwent a hysterectomy. Design: A cross‐sectional design was adopted. Methods: Two hundred and twenty‐five middle‐aged women who were waiting for catheterisation examinations because of possible coronary artery disease were selected. These patients were divided into premenopausal ( n = 41), postmenopausal ( n = 143) and women who had undergone a hysterectomy groups ( n = 41). The differences in the risk factors for coronary artery disease between patients with coronary artery disease (catheterisation results showing stenosis of >50% in at least one major coronary artery) and those without coronary artery disease in the three groups were compared. Results: The participants were aged 56·8 ± 5·9 years. In the premenopausal group, the odds of coronary artery disease among ever or current smokers was 8·46 times the odds of coronary artery disease for the never smokers. In the postmenopausal group, the odds of coronary artery disease among diabetes patients was 2·89 times the odds of coronary artery disease for those without diabetes. Each additional point on the Chinese Beck Depression Inventory‐II increased the risk of coronary artery disease by 5%. In the hysterectomy group, each additional increase in 1 mmHg in systolic blood pressure increased the risk of coronary artery disease by 4%. Conclusions: Smoking, diabetes, depression and systolic blood pressure are predictors of coronary artery disease in middle‐aged women at premenopause, postmenopause and after undergoing hysterectomy respectively. Relevance to clinical practice: These results are beneficial for middle‐aged women at various menopausal stages to effectively implement prevention of coronary artery disease. These findings were among women being evaluated for possible coronary artery disease, we suggest the need for further study in lager, longitudinal studies.